2004
DOI: 10.1002/marc.200400188
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic Effect on Secondary Phase Separation in an Epoxy Resin Modified with Polyethersulfone

Abstract: Summary: The evolution of the morphologies in blends of epoxy/4,4′‐methylenebis(2,6‐dimethylaniline)/polyethersulfone was followed by time‐resolved light scattering, optical microscopy and scanning electron microscopy. The results suggest that, once the diffusion of epoxy molecules cannot follow the geometrical growth, a secondary phase separation occurs, even in the droplet morphology, in which the size of the epoxy‐rich domain grows as usual. The viscoelastic effect of polyethersulfone is also discussed.Deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 18 publications
2
26
0
1
Order By: Relevance
“…Meanwhile, with the same concentration of PES, the slope value of log q m versus log t decreases with the increase in the amount of ATT (0.74 for A1-20, 0.60 for A2-20, and 0.48 for A4-20); all these values are lower than the value of the slope for the unfilled blend, 25 being similar to the results in refs. [21][22][23].…”
Section: Evolution Of the Phase Morphologies As Determined By Om And supporting
confidence: 86%
See 1 more Smart Citation
“…Meanwhile, with the same concentration of PES, the slope value of log q m versus log t decreases with the increase in the amount of ATT (0.74 for A1-20, 0.60 for A2-20, and 0.48 for A4-20); all these values are lower than the value of the slope for the unfilled blend, 25 being similar to the results in refs. [21][22][23].…”
Section: Evolution Of the Phase Morphologies As Determined By Om And supporting
confidence: 86%
“…The blends with nearly critical PES concentrations (A1-20 and A1-25) display a networklike phase morphology, whereas the blend with a supercritical PES concentration (A1-30) shows a phase inversion morphology, in which the epoxy-rich particles are dispersed in the PES-rich continuous matrix. It can be concluded that, in comparison with the results of our previous study, 25 the incorporation of a small amount of ATT has no dramatic effect on the scope of the critical composition for epoxy/PES blends but diminishes the size of the PES-rich phase greatly, which transforms into a silklike morphology. Fig.…”
Section: Resultsmentioning
confidence: 61%
“…If the geometrical coarsening caused by the high fluidity is too fast for diffusion to follow, it will bring the system out of equilibrium and induces seconddary phase separation. By the simulation, Tang et al [26] indicated that double phase separation phenomena could be attributed to the coupling of hydrodynamics and chemical reaction in the binary mixture with reversible reaction system. The results imply that double phase separation will occur spontaneously in the case of low viscosity and low reaction rate.…”
Section: Introductionmentioning
confidence: 98%
“…This behavior is typical for modified epoxy thermosets, and the terms "epoxyrich" (or α phase) and "thermoplastic-rich" (or β phase) are used in the literature (e.g., [50]). Secondary phase separation may occur or not occur in the system, depending on the viscosity of the matrix [51]. The formation of the secondary phase morphology is typical for systems in which phase separation occurs via the spinodal decomposition mechanism.…”
Section: Modification Of Epoxy Composites With Thermoplasticsmentioning
confidence: 99%